Thoracic Paravertebral Block Decreased Body Temperature in Thoracoscopic Lobectomy Patients: A Randomized Controlled Trial - Yan Y; Geng J; Cui X; Lei G; Wu L; Wang G (Dove Medical Press, 2023)
Yanhong Yan,1 Jiao Geng,2 Xu Cui,1 Guiyu Lei,1 Lili Wu,1 Guyan Wang1 1Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of China; 2Department of Anesthesiology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of ChinaCorrespondence: Guyan Wang, Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, No. 1 Dongjiaomingxiang, Beijing, 100730, People's Republic of China, Tel +86-13910985139, Fax +86-10-58268017, Email guyanwang2006@163.comPurpose: Thoracic paravertebral block (TPVB) may be highly beneficial for thoracoscopic lobectomy patients, but it may increase the risk of hypothermia. Apart from its anesthetic-reducing effects, this randomized controlled trial aimed to investigate the hypothermic effect of TPVB, and thus optimize its clinical use.Patients and methods: Adult patients were randomly allocated to two groups: TPVB + general anesthesia (GA) group or GA group. In the TPVB+GA group, the block was performed after GA induction by an experienced but unrelated anesthesiologist. Both the lower esophageal and axillary temperature were recorded at the beginning of surgery (T0) and every 15 min thereafter (T1-T8), and the end of surgery (Tp). The primary outcome was the lower esophageal temperature at Tp. The secondary outcomes included lower esophageal temperature from T0-T8 and axillary temperature from T0-Tp. The total propofol, analgesics, and norepinephrine consumption and the incidence of adverse events were also recorded.Results: Forty-eight patients were randomly allocated to the TPVB+GA (n=24) and GA (n=24) groups. The core temperature at the end of the surgery was lower in the TPVB+GA group than the GA group (35.90± 0.30°C vs 36.35± 0.33°C, P< 0.001), with a significant difference from 45 min after the surgery began until the end of the surgery (P< 0.05). In contrast, the peripheral temperature showed a significant difference at 60 min after the surgery began till the end (P< 0.05). TPVB+GA exhibited excellent analgesic and sedative-sparing effects compared to GA alone (P< 0.001), though it increased norepinephrine consumption due to hypotension (P< 0.001).Conclusion: Although thorough warming strategies were used, TPVB combined with GA remarkably reduced the body temperature, which is an easily neglected side effect. Further studies on the most effective precautions are needed to optimize the clinical use of TPVB.Keywords: core temperature, peripheral temperature, general anesthesia, warming strategy